Uma noção de dor nos estudos sobre a histeria de Sigmund Freud - Bohmer, Mônica Gonçalves (2008)
In this research, we have investigated the way of thinking of Sigmund Freud about pain, based on Studies in Hysteria, published in 1895. This work aproaches histery specifically, and has a grantee source for studying the proposed theme, as one of the major sympthoms in hysterical patients was some kind of pain. The painful sympthoms showed in the presented clinical cases inside the book were not identified with ease, as the nature of hystery on its own turned it difficult. Freud started to investigate the causes for hysteric pain, by hearing the patients lives history. This new way of treating the patient enabled Freud to create some theories on the origin of the painful sympthoms, as long as the clinical tasks were being developed. As a way of identifying the pressuposed facts for creating these hypothesis, we have analysed some texts which, according to the theme, would be opportunities to reflect about pain. These texts were written by Freud and are previous and contemporary to the book Studies in Hysteria. We have also analysed the researches that were happening during the 19th century, aiming to put in the context Freud s findings and to check the relation of these same findings to the medical thoughts of that time